Ethynylphenyl-Derivatized Free Base Porphyrins: Anodic Oxidation Processes and Covalent Grafting onto Glassy Carbon Electrodes - Senge, Mathias (My University, 2020)
In six of seven cases, direct anodic oxidation of the ethynyl group of an ethynylphenyl-derivatized free-base porphyrin gave modified glassy carbon electrodes in which the porphyrin was strongly surface-bound, most likely in a perpendicular geometry through covalent attachment of the ethynyl group to a surface carbon atom. The porphyrins each contained an ethynylphenyl group in one meso position and varied in the groups present in the other three meso positions. Electrografted 5,10,15,20-tetrakis(ethynylphenyl)porphyrin, H21, which has ethynyl moieties in all four meso positions, has well-defined surface voltammetry and grows to multilayer levels upon repeated cyclic voltammetry (CV) deposition scans. Multilayering was not observed to the same degree for monoethynylphenyl-substituted porphyrins and became progressively less for porphyrins having groups in the 15-meso position that were more protective against ethynyl radical attack. Clean molecular monolayer-level coverage was observed for 5-ethynylphenyl-10,20-bis(3-methoxyphenyl)-15-hexylporphyrin, H25. Owing to the fact that the ethynyl oxidation potential (1.1 to 1.5 V vs ferrocene) is more positive than that of the second macrocycle oxidation, the longevities and follow-up reactions of the porphyrin dications were also studied by CV, chemical oxidation, and optical spectroscopy in homogeneous solution. The primary follow-up products of the doubly oxidized porphyrins, whether surface-bound or in solution, were pyrrole-protonated species that were easily reduced back to the neutral porphyrin.
Keywords: Redox reactions; Reaction mechanisms; Pyrroles; Electrodes; Oxidation